2018
DOI: 10.1186/s12890-018-0738-x
|View full text |Cite
|
Sign up to set email alerts
|

Marked deterioration in the quality of life of patients with idiopathic pulmonary fibrosis during the last two years of life

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a chronic disease with a high symptom burden and poor survival that influences patients’ health-related quality of life (HRQOL). We aimed to evaluate IPF patients’ symptoms and HRQOL in a well-documented clinical cohort during their last two years of life.MethodsIn April 2015, we sent the Modified Medical Research Council Dyspnea Scale (MMRC), the modified Edmonton Symptom Assessment Scale (ESAS) and a self-rating HRQOL questionnaire (RAND-36) to 300 IPF patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 57 publications
3
40
2
1
Order By: Relevance
“…7 Interstitial Lung Disease Unit, Royal Brompton Hospital, London, UK. 8 Boehringer Ingelheim International GmbH, Ingelheim am Rhein, Germany. 9 Boehringer Ingelheim GmbH & Co KG, Ingelheim am Rhein, Germany.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Interstitial Lung Disease Unit, Royal Brompton Hospital, London, UK. 8 Boehringer Ingelheim International GmbH, Ingelheim am Rhein, Germany. 9 Boehringer Ingelheim GmbH & Co KG, Ingelheim am Rhein, Germany.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Registry studies reveal that a low forced vital capacity (FVC) % predicted (ie ≤ 50) is associated with severe symptoms and poor HRQoL, and a significant decline in FVC is associated with worsening symptoms and deterioration in HRQoL [4,7]. Furthermore, as patients with IPF approach acute exacerbation or death, they experience an escalating symptom burden and a rapid decline in HRQoL [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a reduced capacity for exercise based on 6-minute walk test distance (24)(25)(26) or self-reported daily activity (27,28) are associated with increased mortality in patients with IPF. In a recent study of 92 patients in the prospective Finnish IPF registry, patients experienced a considerable deterioration in HRQL in the 2 years before death, particularly related to limitations in physical health and functioning (29).…”
Section: Discussionmentioning
confidence: 99%
“…Según diversos autores (25,26) , el requerir cuidado por un gran número de horas al día impacta en la dimensión psicológica y emocional de la persona con EC, pues el perder la independencia y la autonomía en la ejecución de las actividades básicas de la vida diaria genera en el paciente sentimientos de inutilidad, frustración, rechazo y enojo, entre otros, que pueden influir en la percepción de carga que se tiene. Además, también hay afectación en el contexto familiar y en la apreciación del paciente de sentirse como una carga, como consecuencia de las altas demandas de cuidados directos que ocasionan cambios en las dinámicas o roles familiares (27) .…”
Section: Discussionunclassified